Manajemen Strategi dan Penjaminan Mutu untuk Pendidikan Berkelanjutan: Tinjauan Sistematis Literatur - Miftahul Jannah; Muhammad Eko Nurfaiz; Hikmah Kamila Salsabyla Az; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The quality of education is a crucial issue that continues to receive attention in facing the challenges of globalization, digitalization, and the demands of 21st century competencies. Quality improvement efforts are not only related to the quality of students' learning outcomes, but also concern the role of leadership, management effectiveness, and the implementation of a quality assurance system. This study aims to identify strategies to improve the quality of education that have been studied in the literature for the last five years (2020-2025) and answer two research questions, namely: (1) what quality strategies are predominantly discussed in the literature, and (2) how the role of leadership, strategy management, and quality assurance in supporting the quality of education. The method used is literature review with a qualitative approach. Data was obtained from Google Scholar and Publish or Perish (PoP) databases using the keyword